Still alive - Lau, Eng Seng (Nanyang Technological University, 2020)
‘Still Alive’ is a photography project that provides a commentary on the effect of global warming, our overboard usage of plastics in particular. The main idea of this project is to create a level of awareness to the public, that plastics can come in many different forms and how we overlooked and overused the disposable tableware blinded by convenience. The goal of this project is to educate and inspire the audiences to be mindful of our plastics consumption through photography.